Η παρουσία και το κίνημα του πιγκέρνη Αλεξίου Φιλανθρωπηνού στη Μικρά Ασία (1293-1295). Ένα παράδειγμα αποκλίσεων στις ιστορικές εκτιμήσεις του Παχυμέρη και του Γρηγορά - ΓΕΩΡΓΙΑΔΟΥ, Βασιλική (Byzantina Symmeikta, 1996)
Vassiliki Georgiadou The pinkernes Alexios Philanthropenos in Asia Minor and his revolt Considering the two main historiographical sources of the thirteenth century, i.e. George Pachymeres and Nicephorus Gregoras, especially on the point where these sources narrate the movement of Alexios Philanthropenos, one can find out multiple deviations among them. The interesting is that these deviations appear on the points the reader expects to form an opinion about the fact. For example, Pachymeres considers the presence of Alexios Philantropenos in Asia Minor as being indispensable while Gregoras considers it as a necessary solution; Pachymeres considers the motivations of the rebels as a political act with feasible aims while Gregoras considers it being an act of foolishness, condemnable by God; Pachymeres considers his impact being important while Gregoras considers this being inexistent etc. The obviously positive attitude of Pachymeres against the obviously negative one of Gregoras, emerging from the crossreference of these examples, is becoming more apparent when each historian tries to estimate the consequences of this movement. Thus, Gregoras considers this uprising as being a misfortune for the Byzantine Εmpire while Pachymeres considers as a misfortune its suppression.